Compositeur-librettiste : choix ou nécessité ? - Aude Ameille (Revue LISA)
After World War II, an increasing number of composers came to write their own libretti. This paper inquires into the reasons why a composer should decide to make such a choice, considering the benefits but also the risks it involves.